Compulsory Licensing in the Pharmaceutical Market: History and Practice - K. Yu. Sasykin (Сибирское юридическое обозрение, 2022)
In the pharmaceutical industry, the development of a new invention – a drug, the acquisition of a patent and the introduction into civil circulation by the developers spend significant resources in material and time. In this regard, drugs are attractive for falsification, and attempts are also being made to reproduce the imitation of original drugs, which requires special attention to the protection of the rights of patent holders. Obtaining a patent for an invention provides an exclusive right to its owner, being a kind of state gratitude for ensuring innovative progress, and, on the other hand, carries significant threats due to the possible dishonesty of patent owners, which, according to the Author, taking into account the latest challenges of the time, requires no less attention in terms of providing protective mechanisms against abuse. Since the availability of medicines is one of the main tasks of national health care, the Author raised the actual problem of applying one of these mechanisms in domestic law, namely the mechanism for issuing compulsory licenses for medicines as inventions (compulsory licensing). The article contains a brief historical outline of the foreign application of such institutions, analyzes domestic regulation and law enforcement practice, on the basis of which theses are put forward on the need for additional legal regulation.